HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PADA IBU HAMIL PRIMIGRAVIDA TRIMESTER III DI PUSKESMAS KOTA JAMBI - Amalia Damai Fatrin; Muthia Mutmainnah; Meinarisa Meinarisa; Sri Mulyani; Fadliyana Ekawaty (Jurnal Multidisipliner Kapalamada, 2026)
The third trimester of a first pregnancy is a challenging period for a woman, during which various physical and psychological changes can trigger anxiety in anticipation of childbirth. These emotions are often mixed, ranging from happiness in welcoming the baby to concerns about the delivery process. Anxiety is a natural response to the body’s adaptation and the emotional demands experienced during pregnancy. Support from family, whether through attention, encouragement, or emotional presence, plays a crucial role in reducing anxiety levels among pregnant women. This study aims to empirically examine the relationship between family support and anxiety in primigravida women during the third trimester. The research employed a non-experimental approach with a correlational design using a Cross-Sectional method. The results indicate that stronger family support is associated with lower levels of anxiety among primigravida women, highlighting the essential role of family in maintaining psychological well-being throughout pregnancy.